Effect of Standardized Guidelines on Nurses' Knowledge and Practices Regarding Prevention of Infection in Burn Patients - Rabia Bibi, Kousar Parveen, Muhammad Afzal, Sadia Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Burn injuries bear a considerable public health issue all over the world and it is considered among the most distressful and painful injuries. Objectives: To assess the effect of standardized guidelines on nurse's knowledge and practices regarding the prevention of infection among burn patients. Methodology: This cross sectional study was carried out in the burn unit of BVH Bahawalpur in collaboration to the University of Lahore from July 2021 to March 2022 on stastically calculated sample of 95 nurses. After taking the ethical approval and informed consent a questionnaire was used to collect the data. Then an educational intervention was provided to all the participants by dividing in groups three days a week in total 16 weeks. Post-intervention data was collected by using the same questionnaire. Data was entered and analyzed by using SPSS. Results: A total of 95 nurses were included in present study consisting of 15 (15.8%) male nurses and 80 (84.2%) female nurses in this study. Overall mean age of nurses remained to be 37.14±8.51 years. A poo knowledge and practices were revealed in pre-intervention group while significant improvement (p<0.05) was observed for both in post-intervention group. Conclusion: At present poor knowledge and unsatisfactory practices of nurses were revealed in a tertiary care hospital however, a great improvement was observed after intervention in a kind of educational intervention and practical observation.